Evaluation of Urban Plant Vegetation on the Effects of Flight Noise Around the Airport Area - Putra, Dimas Endrawan; Dewantoro R, Daniel; Prayitno, Hadi; Rubiono, Gatut; Wisnu, Kuncoro (PT Inovasi Pratama Internasional, 2024)
In urban and industrial regions, noise pollution is becoming a bigger environmental issue, particularly around airports. Excessive noise can have a number of detrimental effects on people's physical and mental well-being. The World Health Organization (WHO) states that extended exposure to noise can raise blood pressure, cause sleep disruptions, cause hearing loss, and increase the risk of cardiovascular disease. The fast expansion of air travel and heightened airport operations in Indonesia have made the noise issue worse. A lot of study has been done on how to lessen airport noise. More environmentally friendly natural solutions, such as the use of plants as noise barriers, have attracted attention as effective and sustainable alternatives. It is hoped that this research can provide practical and effective solutions that not only reduce noise but also support environmental sustainability. Thus, the results of this research will provide long-term benefits for the community around the airport and educational institutions such as the Indonesian Aviation Academy Banyuwangi. With an average noise reduction percentage of 46.79%, the study's results demonstrate the most notable decrease in noise levels. With a noise reduction of 29.54%, Tunas Merah comes in second. With a noise reduction of 23.94%, the TFan spruce comes in third. Noise is only decreased by 17.77% in the absence of barrier plants.